(NfRANCUZSKO(B-(NRUSSKIJ TEHNI^ESKIJ SLOWARX (B:s (NoKOLO (B80000 (NTERMINOW (B/s - (NbOLOTIN(B, (NaNATOLIJ aNDREEWI^s; (NwOROPAEW(B, (NnIKOLAJ dMITRIEWI^s; (NgORBUNOW(B, (NaLEKSANDR wIKTOROWI^s ((NmOSKWA (B:s (NrUSSO(B,s, 1998)
(NsLOWARX PREDNAZNA^EN DLQ SAMYH [IROKIH KRUGOW NAU^NYH I INVENERNO(B-(NTEHNI^ESKIH RABOTNIKOW(B, (NPEREWOD^IKOW(B, (NPREPODAWATELEJ I STUDENTOW WYS[IH U^EBNYH ZAWEDENIJ RAZLI^NOGO PROFILQ(B.s
Keywords: (NfRANCUZSKIJ QZYKs; (NtEHNIKA I TEHNI^ESKIE NAUKI (B((NW CELOM(B) - (NtERMINOLOGI^ESKIJ SLOWARXs; (NtERMINOLOGIQ TEHNI^ESKAQ (B- (NsLOWARI (B- (NrUSSKIJ QZYKs